Meningkatkan Kemampuan Pra Menulis Menggunakan Media Kolase Pom-Pom Pada Murid Gangguan Spektrum Autisme - Nurul Fitri; Mega Iswari; Rahmahtrisilvia Rahmahtrisilvia; Endang Sri Handayani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Pre-writing skills are essential basic skills for students with autism spectrum disorders because they serve as the foundation for developing writing skills. However, some students with autism spectrum disorders still experience difficulties in fine motor coordination, following patterns, and controlling hand movements during pre-writing activities. This study aims to determine the improvement of pre-writing skills in students with autism spectrum disorders through the use of pom-pom collage media. This study used an experimental method with a Single Subject Research (SSR) approach with an A-B design consisting of a baseline phase (A) and an intervention phase (B). The subject of the study was a student with autism spectrum disorders at SLB Autisma YPPA Padang. Data were collected through performance tests and analyzed using visual graphic analysis based on directional trends, level changes, and data stability. The results showed that pre-writing skills increased after intervention using pom-pom collage media. In the baseline phase, the subject's ability was at 30%, while in the intervention phase it increased gradually to 86%. This improvement indicates a change in better pre-writing skills after the use of pom-pom collage media. Pom-pom collage media can be an alternative learning method to train pre-writing skills in students with autism spectrum disorders.